Vaginal flora in preterm premature rupture of membranes and their sensitivity to commonly used antibiotics - Rani, Shikha; Mehra, Reeti; Gupta, Varsha; Huria, Anju; Chander, Jagdish (Asian Journal of Medical Sciences, 2014)
Background: Ascending infection is one of the most common etiologies in preterm premature rupture of membranes (PPROM). Antibiotics are used in PPROM to prolong the pregnancy and to prevent infection. But to prevent drug overuse and resistance, microorganism directed antibiotics should be used. So, this study was planned to evaluate vaginal flora in pregnant women with PPROM and their sensitivity to commonly used antibiotics. Methods: In this prospective cross-sectional study, 50 pregnant women (cases) preterm premature rupture of membranes and 28 pregnant women (controls) without complication were assessed for the type of vaginal flora and its sensitivity to commonly used antibiotics. Results: Among cases 18 (36%) women showed bacteria on Gram’s staining of vaginal swabs with Gram?negative bacteria (10/18) being the most common. Among controls, 16 (57%) women showed bacteria on Gram’s staining with Gram?positive bacteria being most common. Among cases Escherichia coli and Staphylococcus aureus were the commonest isolates. Of 8 (16%) positive bacterial cultures in cases, 6 (10%) were sensitive to Gentamicin and 2 (4%) to Ampicillin. Conclusion: Lower genital tract flora of pregnant women with PPROM predominantly consists of Gram?negative bacteria, which are sensitive to Gentamicin. DOI: http://dx.doi.org/10.3126/ajms.v5i4.9889 Asian Journal of Medical Sciences 2014 Vol.5(4); 58-60